Rice yellow mottle virus (RYMV) resistance-breaking risk map for Africa - CGIAR Research Program on Rice (2018)
Virulence mutations that are present in a small proportion of the virus population can be sufficient for resistance breakdown. RYMV strains can overcome the RYMV resistance genes and alleles. We established a resistance-breaking risk map to optimize strategies for the deployment of sustainable and resistant rice lines in Africa.